Pengaruh Strategi Promosi Produk, Kualitas Pelayanan dan Citra Perusahaan terhadap Kepuasan Nasabah - M. Fathrezza Imani; Ria Anisatus Sholihah (Velocity: Journal of Sharia Finance and Banking, 2023)
To determine the impact of product promotion methods, service excellence, and company image on customer satisfaction, this study used a quantitative research technique. The study's participants are Bank Jateng Kajen Branch Office customers who reside in the Pekalongan Regency region. Accidental sampling is the sampling method employed. Both primary and secondary data were employed as sources of information in this investigation. Respondents who had completed questionnaires based on library research were provided books, articles, papers, research journals, and other resources pertinent to the study's subject. The Likert Scale method was employed in the data analysis process, which was followed by the execution of many tests, including the Data Quality Test, the Classical Assumption Test, the Multiple Linear Regression Test, the Hypothesis Testing, and the Coefficient of Determination Test. According to the preliminary results of the tests done for this study, product advertising methods have little effect on customer satisfaction, but service quality and a company's image do. Then it was concurrently claimed that 73.9% of customer happiness is influenced by product promotion strategy, service quality, and company image.